REVITALISASI KAWASAN TEPIAN AIR STUDI KASUS KOTA LAMA, KENDARI - , Asrun Safiuddin ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The development of cities in Indonesia canât be separated from the history of the city as the waterfront city. It can be seen the history of the kingdoms of the archipelago in the past. During developing, the cities waterfront suffered, as a function and to urban image due development and the center of a new activity outside the waterfront area. Old Town was once of the government center of Kendari, which the buildings containing a historical value, now is not functional optimally. Mostly the buildings are seen not maintained, memorable uninhabited, and even though as deserted like a ghost town, it is very pronounced, especially at night. Seeing this conditions that occur in the Old City like this, it is necessary to attempt preserve the availability and improve the condition of both the physical environment, social, economic as well as the Old City. The method used in this research is descriptive qualitative analysis, where the data sources explored through direct observation to the field and data from the government. The next conclution that anlysis by the theory associated with the element forming region and as well as theories related with the waterfront. The results showed that the physical condition of the elements forming the Old City does not have a significant influence on the region, this is due to a physical building, infrastructure, and environment. Recommendations focus on the development and direction of these factors. This is consistent with the revitalization program in an effort to renew and improve the quality of forming elements for the development of the Old Town area as a historical waterfront.